Situation Report: Czechoslovakia, 25 August 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Economy at the Half-Year Mark The Burden of Nuclear Power Private Initiative under Strict Control Brezhnev and Husak Mention the CMEA Summit Delays in CMEA Transactions Cause Problems Snippets, but Not Altogether Uninteresting